2015
DOI: 10.1159/000434649
|View full text |Cite
|
Sign up to set email alerts
|

Activated Protein C-Resistance Determination and Vascular Access Thrombosis in Populations with High Prevalence of Factor V Leiden

Abstract: Background/Aims: Factor V Leiden heterozygosity occurs in 3-8% of the general European and US populations. Activated protein C resistance (APC-R) - a non-molecular laboratory test - can efficiently demonstrate the presence of this mutation and can be performed on most coagulation analyzers. On the other hand, fistula or graft thrombosis is a common and costly complication in hemodialysis patients. Our aim was to establish the value of APC-R determination in hemodialysis patients by assessing the risk of access… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
(26 reference statements)
0
2
0
Order By: Relevance
“…It seems that not all known factors increasing blood clotting (e.g., cancers, some autoimmune diseases, obesity, thrombophilia, respiratory and heart failure – NYHA class III and IV) are important for maintaining patency of catheter. Moreover, especially in a part of patients with recurrent thrombosis undiagnosed thrombophilia can be anticipated [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…It seems that not all known factors increasing blood clotting (e.g., cancers, some autoimmune diseases, obesity, thrombophilia, respiratory and heart failure – NYHA class III and IV) are important for maintaining patency of catheter. Moreover, especially in a part of patients with recurrent thrombosis undiagnosed thrombophilia can be anticipated [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The sustained maintenance of VA patency without flow dysfunction is essential and can affect the prognosis of patients undergoing HD. 1 Thus, several studies have assessed the risk factors associated with VA thrombosis and/or loss and revealed that many risk factors such as age, 21 sex, 22 the presence of DM and hypertension, 3,15,21 the use of drugs with antiplatelet and/or vascular antiproliferative activity, 23 and AVF location 9 Our study had several limitations. First, it was a retrospective, single-center, observational study, which might not apply to the general population with ESRD undergoing HD.…”
Section: Journal Of Medicine and Life Sciencementioning
confidence: 89%